2020
DOI: 10.2174/1570159x17666191113100808
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: The New Challenge for Traumatic Brain Injury Diagnosis

Abstract: The acronym TBI refers to traumatic brain injury, an alteration of brain function, or an evidence of brain pathology, that is caused by an external force. TBI is estimated to become the third leading cause of permanent disability and mortality worldwide. TBI-related injuries can be classified in many ways, according to the degree of severity or the pathophysiology of brain injury (primary and secondary damage). Numerous cellular pathways act in secondary brain damage: excitotoxicity (mediated by excitatory neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 153 publications
(148 reference statements)
0
16
0
Order By: Relevance
“…MSCs, which is thought to be the most optimum candidate to treat the neurodegeneration disease, no matter injecting cells directly or the extracellular vesicles (exosomes) 89 , 134 , striking improvement in both neurogenesis or recovery of the function have been acquired 135 , 136 . Furthermore, a host of ncRNA are involved in the TBI diagnosis and treatment 137 .…”
Section: The Promising Methods For Regulation Of Neuroinflammation Andmentioning
confidence: 99%
“…MSCs, which is thought to be the most optimum candidate to treat the neurodegeneration disease, no matter injecting cells directly or the extracellular vesicles (exosomes) 89 , 134 , striking improvement in both neurogenesis or recovery of the function have been acquired 135 , 136 . Furthermore, a host of ncRNA are involved in the TBI diagnosis and treatment 137 .…”
Section: The Promising Methods For Regulation Of Neuroinflammation Andmentioning
confidence: 99%
“…t-tau levels are elevated at various injury severities 174,203 , and in association with DAI 83,216 , as early as 1 hour after TBI and correlated with positive findings on CT 185,217 , as well as self-reported symptoms after mild TBI 66 . Micro RNA (miRNAs) are small molecules that contribute to gene expression regulation, blood, CSF and brain tissue levels 184,189,[218][219][220][221][222] . It has been demonstrated that miRNA expression is altered across all TBI severities over time periods ranging from 1 hour to several days posttrauma 184,223,224 .…”
Section: 1mentioning
confidence: 99%
“…Transcriptomics is the study of all the RNA transcripts in an individual cell or family of cells, comprising both protein-coding messenger RNA (mRNA) and non-protein-coding RNAs, such as transfer RNA (tRNA), 150 ribosomal RNA (rRNA), 151 microRNA (miRNA), 88 , 152 - 157 enhancer RNA (eRNA), 158 small interfering RNA (siRNA), 159 P-element induced wimpy testis-interacting RNA (piRNA), 160 small nucleolar RNA (snoRNA), extracellular RNA (exRNA), small Cajal body-specific RNA (scaRNA), and long non-coding RNA (lncRNA). 161 Epigenomics is strictly tied to the transcriptome and is often seen as a subfield of transcriptomics.…”
Section: Transcriptomic Biomarkersmentioning
confidence: 99%